Capacity Of Magelang Regency In Protecting The Historical Site Of Mendut Temple From Mount Merapi Eruption - Candra Sholeh Hermawan; Heridadi Heridadi; Bambang Wahyudi; Pujo Widodo; Wilopo Wilopo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Mount Merapi is one of the most active volcanoes in Indonesia, which is administratively located on the western side of the mountain in Magelang Regency. There is a historical site, namely the Mendut Temple in Magelang Regency which was affected by the eruption of Mount Merapi. To reduce the impact of the eruption of Mount Merapi on the historical site of Mendut Temple, capacity and cooperation from stakeholders in the Magelang Regency area are needed. The purpose of this study was to analyze the capacity of Magelang Regency in protecting the historical site of Mendut Temple from Mount Merapi Eruption. This research method uses a qualitative approach with the locus of research conducted in the Magelang Regency area. Data collection techniques through interviews, observation and documentation. As for data checking by triangulation and data analysis techniques using interactive analysis models. The results of the study show that mitigation focuses on structural aspects, especially post-disaster activities by covering tarpaulins while non-structural ones are not optimal due to gaps in coordination, communication and cooperation between agencies. The Mount Merapi disaster risk assessment in increasing the capacity of Magelang Regency through strategic efforts ranging from study procedures or SOPs to well-prepared scenarios and alternatives such as several evacuation signs and symbols. Aspects of innovation and knowledge have been carried out by Magelang Regency through the sister village program to provide information on evacuation with a mutual cooperation system. The Magelang Regency disaster risk factor in the aspect of the policy plan refers to existing regulations and has prepared land for settlements for eruption disaster victims with a grant system from the Magelang Regency Government. Institutional capacity needs to be understood together by collaborating and establishing a shared consensus on the policies to be built.